CUSTOMER’S QUALITY PERCEPTION AND BRAND PREFERENCE OF TELECOMMUNICATION FIRMS IN BAYELSA STATE, NIGERIA - Ademe, D. G.; Opuene, E. J (Scholar Express Journals, 2022)
Telecommunication services have played a critical role in boosting the growth of many sectors of the economy. This study therefore seeks to determine the relationship between customer’s quality perception and brand preference of telecommunication firms in Bayelsa state. Data were collected from four hundred (400) customers of telecommunication firms in Bayelsa state where only 381 of the questionnaire were found valid and useful for analysis using Spearman Rank Correlation Coefficient with the aid of SPSS version 23 to test two (2) formulated hypotheses. Findings show that customer’s quality perception has a strong impact on brand preference of Telecommunication firms in Bayelsa state. The study therefore recommends thatby continuing to deliver high-quality services, telecommunications might acquire and keep consumer satisfaction. Again, telecommunication service providers should also have assessment and incentive systems to guarantee that good performance is tracked and rewarded
Keywords: Information Security; Service Availability; Brand Preference; Customer Satisfaction